Drug Dose Calculator Application to Prevent Medication Errors - Mayang Indah Lestari; Zulkifli Zulkifli; Rizal Zainal; Muhammad Imam Mulia (JAI (Jurnal Anestesiologi Indonesia))
As a part of the essentials in achieving patient safety, medication errors are one of the most financially detrimental problems in the treatment process faced by health institutions. This article firstly debriefs the definition of medication error and its general classification based on the treatment process. Wrong dose calculation has become one of the most frequent medication errors, especially among anesthesiology-care providers. This article then concisely defines the side effects of commonly-used anesthesia drugs in critical and perioperative care. This article examines medication errors prevalence among anesthesiologists and investigates the line between several risk factors and wrong dosage calculation. Finally, this article concludes with the elucidation of current trends of drug dosage calculators and several studies that aim to validate and prove the efficacy of those applications.